BIMBINGAN BELAJAR BAHASA INGGRIS GRATIS UNTUK SISWA MI YA BUNAYYA HIDAYATULLAH MANOKWARI - Syahira Syahira; Heriyanti Heriyanti (LP4MK STKIP PGRI Lubuklinggau, 2022)
It is undeniable that English is one of the subjects that is a scourge for most students. On the other hand, whether we realize it or not, English is indispensable in various aspects of science and everyday life. This activity aims to provide assistance to students at MI Ya Bunayya Hidayatullah Manokwari. Mentoring activities are carried out by providing private tutoring. In each activity students are separated into small groups of 1-3 people according to their respective grade levels. With this method, all students can participate in more intensive learning activities. If you pay attention, it can be seen that the enthusiasm and motivation of students to learn is increasing. It is hoped that this activity can trigger the enthusiasm of the students to enjoy and learn English more.